ІДЕНТИФІКАЦІЯ АКТИВНИХ ОПОРІВ АСИНХРОННОГО ДВИГУНА ЗА ДОПОМОГОЮ АДАПТИВНОГО СПОСТЕРІГАЧА ПОТОКОЗЧЕПЛЕННЯ - Пересада, С.М.; Коноплінський, М.А. (Інститут електродинаміки НАН України, Київ, 2012)
The new algorithm, which provides an exponential identification of active resistances of stator and rotor of induction motor and based on information about stator current, voltage and rotor angular velocity, was synthesized using the Lyapunov’s second method. Local asymptoticity of active resistance identification under persistance of excitation conditions was theoretically proved. Additionally, the synthesized algorithm of identification is an observer of the rotor flux linkage, adaptive to changes of stator and rotor resistances. The simulation results and experimental tests confirm the efficiency of the proposed identification algorithm. References 5, figures 11.